Ihe description of the subject of group forms of cognitive activity organization in higher pedagogical educational institutions (Pedagogy of Higher and Secondary Education, 2013)
Dudnik A. О. Ihe description of the subject of group forms of cognitive activity organization in higher pedagogical educational institutions.The article dwells upon characteristics of a subject concerning group forms of cognitive activities organization in terms of higher pedagogical establishment, the specificity of group forms of students’ cognitive organization in terms of higher pedagogical educational establishments has been also specified in the article.
Keywords: a teacher’s-to-be-readiness; professional activities; professional competence; professional-and-pedagogical training